The Quality Instinct: Seeing Art Through a Museum Director's Eye - Anderson, Maxwell L. (Rowman & Littlefield Publishers, 2012)
How do we judge what is good in art? Or more to the controversial point, can we judge art? Acclaimed museum director Maxwell Anderson, newly named Eugene McDermott Director of the Dallas Museum of Art, enters the fray with The Quality Instinct. Part personal memoir, part thinking person's guide to the museum, The Quality Instinct is filled with wit and humor, anecdotes, and insights from the author's 30 years in the highly competitive, often contentious art world. Anderson takes us on a grand tour of ancient and contemporary art, sharing five simple metrics of quality that help us to increase our "visual literacy" as we learn to see, not simply look and judge.